2003
DOI: 10.1021/es0340679
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Variations of Mercury in Tuna

Abstract: While the bulk of human exposure to mercury is through the consumption of marine fish, most of what we know about mercury methylation and bioaccumulation is from studies of freshwaters. We know little of where and how mercury is methylated in the open oceans, and there is currently a debate whether methylmercury concentrations in marine fish have increased along with global anthropogenic mercury emissions. Measurements of mercury concentrations in Yellowfin tuna caught off Hawaii in 1998 show no increase compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 51 publications
8
84
3
1
Order By: Relevance
“…This is in contrast to the hypothesis that most of the MMHg in marine fish results from potential methylation sources in the deep ocean such as hydrothermal systems and sediments (Kraepiel et al, 2003). Although the source of MMHg in marine fish is largely unknown, Rolfhus and Fitzgerald (1995) greater than those estimated for the shelf sediments sampled in this study.…”
Section: Sediment−water Flux Of Mmhgcontrasting
confidence: 85%
See 1 more Smart Citation
“…This is in contrast to the hypothesis that most of the MMHg in marine fish results from potential methylation sources in the deep ocean such as hydrothermal systems and sediments (Kraepiel et al, 2003). Although the source of MMHg in marine fish is largely unknown, Rolfhus and Fitzgerald (1995) greater than those estimated for the shelf sediments sampled in this study.…”
Section: Sediment−water Flux Of Mmhgcontrasting
confidence: 85%
“…This means that the biogeochemistry and bioaccumulation of MMHg in nearshore and continental shelf areas may be major factors affecting the exposure of humans to MMHg. However, and unfortunately, little is known about the production and cycling of MMHg in coastal marine systems and the open ocean, where most of the MMHg in biota has been hypothesized to result from production in deep sea sediments and/or hydrothermal systems (Kraepiel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The size of a fish is known as a determining factor of its Hg burden (Mackay et al, 1975;Jaffar and Ashraf, 1988;Bloom, 1992;Dietz et al, 1996;Gilmour and Riedel, 2000;Stafford and Haines, 2001;Kraepiel et al, 2003), and has been confirmed here.…”
Section: Mercury Size Sex Species and Locationsupporting
confidence: 76%
“…These interspecific differences in Hg levels were probably linked to differences in each species physiology, feeding rate, growth rate, lifespan, migratory patterns, foraging habits and/or diet. For instance, the low Hg levels in Wahoos could be explained by the surface foraging habits of this species (0-12 m) which contrasts with the others which feed from the surface to great depths (up to 800 m for Swordfish) where Hg methylation, in these poorly oxygenated waters, enhances its bioaccumulation (Monteiro et al, 1996;Kraepiel et al, 2003). A clear example of differential vertical distribution of Hg levels in fish is given by Monteiro et al (1996), who found a 4-fold increase in Hg levels from epipelagic (100-150 m) to mesopelagic (300-1 200 m) lanternfish species in the sub-tropical mid-North Atlantic.…”
Section: Mercury Size Sex Species and Locationmentioning
confidence: 99%
“…MMHg production in the oxygen minimum zone (OMZ) of the oceanic water column has been hypothesized 7,13 and recent field studies have offered new evidence supporting in situ methylation not only in OMZs (refs 3,6) but also in oxic surface waters 4,5,[15][16][17] . Vertical differences in ocean biogeochemistry and the relative contributions of different Hg sources to the overall MMHg burdens in fish have wide-ranging implications for understanding how MMHg levels in marine biota will respond to future changes in anthropogenic Hg emissions 3,18 .…”
mentioning
confidence: 99%